2016
DOI: 10.1007/s11154-016-9362-3
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine manifestations of systemic mastocytosis in bone

Abstract: Systemic Mastocytosis (SM) is characterized by accumulation of clonal, neoplastic proliferations of abnormal mast cells (MC) in one or more organ system other than skin. Presence of these multifocal clusters of abnormal mast cells is an essential feature of SM. Frequently associated with D816V (KIT) mutation, the presence of this mutation and elevated serum tryptase are minor criteria for diagnosis. SM manifestations depend on the degree of mast cell proliferation, activation and degranulation. SM has a variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
2
22
0
2
Order By: Relevance
“…Mast cells are now considered critical in allergy [100] and innate immunity in the skin [138,139] but also for immunity [101,140] and inflammation [141][142][143][144]. The possible role of CRH in cutaneous inflammatory diseases has also been reviewed [56,85].…”
Section: Stress Crh and Immune Cellsmentioning
confidence: 99%
“…Mast cells are now considered critical in allergy [100] and innate immunity in the skin [138,139] but also for immunity [101,140] and inflammation [141][142][143][144]. The possible role of CRH in cutaneous inflammatory diseases has also been reviewed [56,85].…”
Section: Stress Crh and Immune Cellsmentioning
confidence: 99%
“…Several case studies and small clinical trials described a reduced bone mass and an increased fracture occurrence in patients with MC accumulation in the bone marrow (143)(144)(145)(146). Larger cohort studies confirmed the high prevalence of osteoporosis (up to ∼60%), and fragility fractures (up to ∼40%) in SM patients (147-150), as recently reviewed in more detail by Greene et al (151). The pathomechanisms of MC-induced bone loss are not yet fully understood.…”
Section: The Role Of Mast Cells In Bone Disorders Osteoporosismentioning
confidence: 89%
“…Auffällig war jedoch eine deutlich erhöhte Tryptase von 71 µg/l (Norm < 11,4), sodass der Verdacht auf eine systemische Mastozytose als weitere Ursache der Osteoporose gestellt wurde. [6,7]. Als Osteoporosetherapie wird aufgrund der aktuellen Studienlage eine antiresorptive Therapie mit Bisphosphonaten empfohlen.…”
Section: Fallbeschreibungunclassified